2020
DOI: 10.5114/jcb.2020.98108
|View full text |Cite
|
Sign up to set email alerts
|

Eye plaque brachytherapy versus enucleation for ocular melanoma: an analysis from the National Cancer Database

Abstract: Purpose: There is no current randomized data comparing the efficacy of brachytherapy and enucleation for patients with larger sized tumors. The purpose of the present study was to use a large, contemporary database to determine current practice patterns and compare survival outcomes between different management options for patients with choroidal melanoma of various sizes. Material and methods: The National Cancer Database was queried (2004-2014) for histologically-confirmed choroidal melanoma for patients tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Therefore, local treatments other than enucleation, such as eye plaque brachytherapy, should be safe and efficient in patient's vision and aesthetics preservation. Their findings suggest that eye plaque brachytherapy is a reasonable treatment option for all size ocular melanoma tumors, even large size tumors [28]. The above observation may also confirm our results, such as the lack of differences in OS and CSOS, irrespectively of the ring melanoma treatment manner.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, local treatments other than enucleation, such as eye plaque brachytherapy, should be safe and efficient in patient's vision and aesthetics preservation. Their findings suggest that eye plaque brachytherapy is a reasonable treatment option for all size ocular melanoma tumors, even large size tumors [28]. The above observation may also confirm our results, such as the lack of differences in OS and CSOS, irrespectively of the ring melanoma treatment manner.…”
Section: Discussionsupporting
confidence: 87%
“… 5 A recent large national retrospective study showed that large uveal melanoma treated with EPBT had comparable survival to enucleation. 6 Genomic data supports this assertion, in that micrometastases have typically already occurred in patients who present with large tumors with aggressive genetic signatures. 7 Additionally, 2 prior retrospective studies evaluating EPBT for large uveal melanoma showed acceptable local failure rates (6%-9%) at 5 years.…”
Section: Introductionmentioning
confidence: 82%
“…Although current American Brachytherapy Society (ABS) guidelines stipulate that EPBT may be used for large uveal melanoma if basal diameters do not exceed the limits of brachytherapy and there is ≤5 mm extraocular extension, there are no randomized controlled trials comparing EPBT to enucleation for large uveal melanoma (5). A recent large national retrospective study showed that large uveal melanoma treated with EPBT had comparable survival to enucleation (6).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of uveal melanomas includes enucleation or radiation therapy. Radiation therapy may be delivered either via brachytherapy (BT) [4][5][6][7][8][9][10][11][12][13][14][15][16][17], external beam radiation therapy (EBRT), using proton beams or stereotactic radiosurgery with Gamma knife (Elekta Instruments, Stockholm, Sweden). Outcomes [18] are reported in terms of survival, metastases, recurrence, and visual acuity, but there are few EBRT results that include doses to OARs within the optical apparatus [19][20][21].…”
Section: Purposementioning
confidence: 99%
“…Iodine-125-based eye plaque low-dose-rate BT ( 125 I LDR-BT) has proven to provide superior vision retention and equivalent tumor control over conventional enucleation for ocular melanomas [10,[22][23][24]. However, its delivery typically takes 5 days, with a dose-rate of 0.35-0.83 Gy/h.…”
Section: Purposementioning
confidence: 99%